DEVELOPING TEACHING MATERIALS USING 5E MODEL OF INSTRUCTION TO INCREASE STUDENTS’ HIGHER ORDER THINKING SKILLS - Mutrofin, Lilik; Nur, Mohamad; Yuanita, Leny (JPPS (Jurnal Penelitian Pendidikan Sains), 2016)
The aims of this study were to develop teaching materials using 5E model of instruction to increase students’ higher order thinking skills and to describe their feasibility. The teaching materials (i.e. lesson plan, student worksheet, and higher order thinking skills test) were developed using 4-D model that was proposed by Thiagarajan, Semmel and Semmel. The subject of this study were the developed teaching materials that were tried out to undergraduate students of Biology Department, University of Muhamadiyah Surabaya (UMS) and undergraduate students of Chemistry Department, State University of Surabaya (UNESA). The developmental testing was designed using the one-group pretest and posttest design with three times replication. Additionally, each replication used about 15 undergraduate students. Data were collected using experts’ appraisal, observation, test, and questionnaire and analyzed quantitatively and descriptive qualitatively. The findings of this study indicated that the developed teaching materials were feasible. They were valid according to experts’ appraisal, and they were practice and effective to be implemented in the classroom. Penelitian ini bertujuan untuk mengembangkan bahan ajar menggunakan model pembelajaran 5E untuk meningkatkan keterampilan berfikir tingkat tinggi siswa serta mendeskripsikan kelayakan bahan ajar tersebut. Bahan ajar dalam penelitian ini dikembangkan dengan menggunakan  model 4-D yang diusulkan oleh Thiagarajan, Semmel dan Semmel. Subyek dalam penelitian ini adalah bahan ajar yang telah dikembangkan dan diuji cobakan kepada mahasiswa tahun pertama angkatan 2014 di Jurusan Biologi, Universitas Muhamadiyah Surabaya (UMS) dan di Jurusan Kimia, Universitas Negeri Surabaya (UNESA). Desain penelitian yang digunakan ketika uji coba bahan ajar adalah one-group pretest and posttest dengan replikasi sebanyak tiga kali. Selain itu, untuk setiap replikasi menggunakan sekitar 15 mahasiswa. Data dikumpulkan menggunakan penilaian ahli, observasi, tes, dan kuesioner serta dianalisis secara kuantitatif dan deskriptif kualitatif. Penemuan penelitian ini menunjukkan bahwa bahan ajar yang dikembangkan memenuhi kriteria kelayakan, yaitu valid menurut pendapat para ahli, praktis dan efektif ketika diuji cobakan di dalam kelas.